الرسم على القيمة المضافة دراسة تحليلية لنظام الشراءبالإعفاء ضمن النظام الضريبي الجزائري دراسة حالة مؤسسة إقتصادية - محمد هادف; محمد حنابي; محمد دوة (جامعة عمار ثليجي, 2018)
In modern terms, taxation is not only an instrument for achieving the state's financial goals but an effective means of intervening in economic and social life. The global economic developments and the decline of the classical concept of the non-interventionist state, as well as the need to integrate into the international economic environment, necessitated that countries develop their legislation and structure their tax systems to cope with developments. The introduction of the value-added tax is considered the culmination of the development of the tax field. It represents an integrated and harmonious system characterized by simplicity, transparency and efficiency. It provides an effective means of influencing the economic field and provides a clear picture of the tax track. The value-added tax was created in 1954 by French tax inspector Maurice Laurie, who was the deputy director of the Directorate General of Taxation. This project raised considerable controversy, since the skeptics in this system thought that the concentration of the tax would be in the last distribution rings, and after the French financial authorities were convinced of the usefulness of this tax, it was initially applied to large enterprises and then circulated in 1966 for retail activity. After the success of this experiment in France, the European Community gradually introduced it, and then expanded it to the rest of the world. It was adopted by most countries except the United States of America and Canada, which have a similar system. Algeria has adopted the VAT system since 1992, and its first provisions were issued in the Finance Act 1991 to compensate the system of fees on the number of works. The value-added fee was first applied to sales, real estate and services, and later to the liberal professions in 1996 and to retail operations in 2001.